The development of an assessment protocol for activity participation in those suffering from mental illness - Rice, Catherine May (My University, 2012)
Aim: To compile an assessment protocol, comprising of appropriate assessment methods, which can be used to assess activity participation in those suffering from mental illness. Research methods: An audit of existing performance-based instruments was carried out, and thereafter focus groups with clinicians were conducted. The methods of assessment were collected through review of existing performance-based assessments and by means of discussion groups with occupational therapists in mental health care. Following this the Activity Participation Assessment protocol was compiled. The content validity was then investigated through expert review. Results: Assessment methods for the domains of the Activity Participation Assessment were determined. Common methods of assessment included interviewing, activities, collateral information and standardised assessments. The content validity indices for all domains of assessment were above the 0.80 recommendation for new instruments. Conclusion: The Activity Participation Assessment has good content validity and can be used in the clinical setting.
M.Sc. (Occupational Therapy), Faculty of Health Sciences, University of the Witwatersrand, 2011
Keywords: Occupational Therapy; Psycotherapy